Artificial Intelligence in Islamic Educational Perspective: Insights from Said Nursi’s Character Education Concept - Setiawan, Agus; Rahimi, Wildan; Rusiani, Risda; Rabiah, Rabiah (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
Various types of jobs that require a lot of manpower, are now easy to do with the presence of technology. One of the technologies that is massive and highly developed today, and has penetrated into various human sectors is AI (Artificial intelligence), or what is commonly called artificial intelligence. The implementation of the use of AI in education has great potential to change the way learning and educational efficiency are achieved. In the reality that is found today, the use of AI, which should be used for positive things, tends to be negative. The purpose of this study, namely to identify the problem of AI advancement or artificial intelligence and its implications for the character of students, then is relevant to the concept of Said Nursi's character education as an effort to provide solutions to the problem of using AI in Islamic education which has implications for the characteristics of students. The method used in this study is qualitative, through literature review. The results of this study show the impact caused by AI on human characters, such as excessive addiction, loss of human interaction, potential for plagiarism and cheating, in his teaching Said Nursi emphasized the importance of character education, His approach to education is holistic and integrates faith and knowledge, which has significant relevance in the era of artificial intelligence such as holistic education, ethical foundations, integration of science and faith, the role of educators, human-centered AI, and spiritual resilience.